OVERVIEW OF BLIND-CHILDREN CARIES INDEX IN SPECIAL NEED SCHOOLS IN CIMAHI CITY - Sri Sarwendah; Henri Hartman; Muhammad Alfin (Journal of Health and Dental Sciences, 2022)
ABSTRACT Blind people have limitations in receiving dental and oral health information. It can facilitate the occurrence of caries. Blind people have limitations in performing various activities that require vision assistance, such as maintaining oral and dental hygiene when brushing their teeth, so blind people often experience multiple problems with their teeth, one of which is caries. This study aimed to determine the caries index in blind children in SLBN A Cimahi City and SLBN A Bandung City. The study used a cross-sectional design and consecutive sampling. The number of samples was 21 blind children. The study's results on blind children aged 6-12 showed a very low to moderate caries index. The def-t index in children with low vision blindness has moderate criteria; in children with total blind blindness, it has low standards. Children with low vision and total blind have the same DMF-T index, which is low. The def-t index in SLBN A Citeureup Cimahi City has low criteria, while SLBN A Padjadjaran Bandung City has a def-t index with moderate standards. SLBN A Citeureup Cimahi City and SLBN, A Padjadjaran Bandung City, have the same DMF-T index, which is low. Parents, teachers, caregivers, and health workers need to pay more attention to the dental and oral health of blind children. DOI : 10.54052/jhds.v2n2.p365-374